The effect of circuit training of submaximal power on the morphofunctional state and physical performance of qualified athletes - Baryaev, A.A.; Talibov, A.H.; Badrak, K.A.; Kamensky, I.R. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to evaluate the effect of training loads of submaximal power, organized by the circular method, on the functional state of athletes of martial arts, game and complex sports in the preparatory period. Methods and structure of the study. The study was conducted on the basis of the P.F. Lesgaft National State University of Physical Culture, Sports and Health, with the involvement of female athletes from the national teams of the St. Petersburg State University of Industrial Technology and Design. The methods of analysis and generalization of scientific and methodological literature, pedagogical observation, pedagogical testing, mathematical and statistical data processing are used. Results and conclusions. According to the data obtained, an increase in strength endurance and aerobic-anaerobic productivity has been established. Morphofunctional shifts in body composition were revealed – a decrease in resting heart rate and blood pressure, BMI, and the fat component of the subjects were noted. It is shown that parameters such as the proportion of muscle, water mass and psycho-emotional stability increased at the end of the study. The results obtained allow us to conclude that it is advisable to introduce exercises in a circular form of organization, contributing to an increase in the level of general physical fitness.